Four different monoclonal antibodies against type C1 toxin of Clostridium botulinum. - Oguma, K (1982)
Monoclonal antibodies against type C1 toxin produced by Clostridium botulinum type C strain Stockholm (C-ST) were prepared by fusion of BALB/c myeloma cells P3X63-Ag8, with spleen cells from the mice immunized by C-ST toxoid. About 5% of single-cell colonies in wells were found to produce antibodies against the toxin as determined by an enzyme-linked immunosorbent assay (ELISA). Four different hybridoma cell lines, no. 9, 12, 14, and 17, were established, cloned by limiting dilution, and intraperitoneally injected into mice to obtain the ascites fluids containing high-titered antibodies. The reactions of these antibodies to type C1 and D toxins of strains C-ST, D-1873, and D-South African (D-SA) were observed by both neutralization and ELISA tests. Three monoclonal antibodies, no. 9, 14, and 17, reacted with C-ST toxin, but only no. 17 highly neutralized the toxin. These antibodies did not react with type D toxins. On the contrary, no. 12 reacted with toxins of both C-ST and D-SA (but not of D-1873) and commonly neutralized these two toxins. This indicates that there is a common antigenic part between C-ST and D-SA toxin molecules which participates in the toxin-neutralizing reaction. The neutralization profiles of C-ST toxin by no. 12 and 17 antibodies were different in a time-to-death test of mice. The mechanisms of neutralization by no. 12 and 17 may be different.